CHRONIC DIARRHOEA: NOT A RARE PRESENTATION OF VITAMIN B 12 DEFICIENCY - Adil, Noreen; Mehraj, Adil; Khan, Jamila; Bhutta, Sohail; Jamil , Muzamil; Aslam, Mujahid (Journal of Ayub Medical College Abbottabad, 2024)
Background: Diarrhoea is defined as stool frequency of more than three times in twenty-four hours or a stool weight of more than two hundred grams and it is labelled as chronic diarrhoea if it persists for more than four weeks. Chronic diarrhoea is a common gastrointestinal problem worldwide that affects three to fifteen percent of population. Objective was to determine the efficacy of vitamin B 12 replacement in treatment of chronic diarrhoea in vitamin B deficient patients. It was a Quasi-experimental study carried out at Pakistan Ordinance Factory (POF) Hospital Wah Cantt, from September 2023 to February 2024. Methods: All the new patients of chronic diarrhoea of ages between 12-65 years who had low serum vitamin B 12 and normal serum folate levels were included in the study. The patients were booked from Medicine and Allied outpatient and they were given parenteral vitamin B12. The sub-set of patients in whom diarrhoea was settled was followed up till six months. The efficacy was defined as settlement of diarrhoea with parenteral vitamin B12 within one week. The secondary outcomes were adequacy of serum vitamin B12 levels at 2 weeks, three months and six months after treatment. All patients (100%) had adequate B12 levels till follow up. Data was analyzed through SPSS. Results: Efficacy of parenteral B12 supplementation was seen in 16 (76.2%) patients. Out of sixteen patients who responded to vitamin B12 supplementation, 10 (47.6%) patients showed improvement in less than two days, 5 (23.8%) showed improvement in less than four days and 1 (4.8) patient stopped experiencing diarrhoea within seven days of intramuscular vitamin B12 with p-value of <0.001. Conclusion: Replacement of vitamin B 12 in patients with chronic diarrhoea having low vitamin B 12 results in settlement of diarrhoea.